2016
DOI: 10.1007/s12160-015-9758-4
|View full text |Cite
|
Sign up to set email alerts
|

An HIV Testing Intervention in African American Churches: Pilot Study Findings

Abstract: Background African Americans are disproportionately burdened by HIV. The African American church is an influential institution with potential to increase reach of HIV prevention interventions in Black communities. Purpose This study examined HIV testing rates in African American churches in the Taking It to the Pews pilot project. Using a community-engaged approach, church leaders delivered religiously-tailored HIV education and testing materials/activities (e.g., sermons, brochures/bulletins, testimonials) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…The Black Church is one such organization, which continues to play a vital role in the lives of their congregants and surrounding community members [4,5]. More importantly, Black churches have made increasingly positive strides in the incorporation of HIV testing and prevention interventions, programs, and ministries into their venues [6][7][8][9]. Through the co-location of health services, the Black Church could increase access and availability of HIV related services for the Black community [2].…”
Section: Introductionmentioning
confidence: 99%
“…The Black Church is one such organization, which continues to play a vital role in the lives of their congregants and surrounding community members [4,5]. More importantly, Black churches have made increasingly positive strides in the incorporation of HIV testing and prevention interventions, programs, and ministries into their venues [6][7][8][9]. Through the co-location of health services, the Black Church could increase access and availability of HIV related services for the Black community [2].…”
Section: Introductionmentioning
confidence: 99%
“…implement, evaluate, and disseminate the religiously-culturally tailored intervention (Taking It to the Pews [TIPS]). Feasibility and outcome studies indicated that TIPS yielded much higher HIV testing rates (42% versus 59%) than a non-tailored control condition, respectively (Berkley-Patton et al, 2016, 2019. Inclusion of faith leaders/church members in the research process has also been intended to increase ownership and maintenance of the intervention, while increasing the capacity of churches to address existing and emerging health concerns of importance to church and community members.…”
Section: Journal Of Participatory Research Methodsmentioning
confidence: 99%
“…Community-based participatory research (CBPR) has been used in the U.S. as an approach to address health inequities by engaging faith community members in addressing the health of underserved congregants and community members (Israel et al, 2005(Israel et al, , 2013. CBPR-driven health promotion interventions have addressed many health concerns in faith-based settings, such as HIV/STDs (Berkley-Patton et al, 2016Derose et al, 2016), fruit/ vegetable intake (Campbell et al, 2007), colorectal cancer (Lumpkins et al, 2013), and blood pressure (Whitt-Glover et al, 2017). In these and other studies, faith members have assisted with determining study procedures, recruiting and retaining participants, interpretation of results, and dissemination of research findings.…”
mentioning
confidence: 99%
“…Moreover, religious participation has a positive impact on adolescents: those scoring higher in religiosity are less likely to be sexually active than those scoring lower in religiosity [21]. Although qualitative research [22,23] suggests that African American churches are interested in providing HIV education and a recent pilot study found that a church-based intervention increased HIV testing [24], few trials [25] have examined HIV interventions or other sexual risk-reduction interventions in African American churches.…”
Section: Implications and Contributionmentioning
confidence: 99%